Examination of Serum Isthmin-1 Levels in Patients with Polycystic Ovary Syndrome - Oz, Zeynep Dila; Atli, Ayse Akmese; Ozdede, Mehmet Ridvan; Bozyil, Ahmed Sait; Sayin, Orhan; Pervin, Mehtap; Kacar, Emine (Wiley, 2025)
[Abstract Not Available]
Keywords: Isthmin-1; Polycystic Ovary Syndrome; Adipokine